2020
DOI: 10.15537/smj.2020.2.24843
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, types and outcomes of sternal wound infections after cardiac surgery in Saudi Arabia

Abstract: Objectives: To determine the incidence, types, risk factors, identify organisms, and assess outcomes of surgical wound infections (SWIs) after cardiac surgery at a tertiary hospital in Riyadh, Saudi Arabia. Methods: This historical cohort study reviewed the chart of patients who underwent cardiac surgery at King Khalid University Hospital, Riyadh, Saudi Arabia between January 2009 and December 2014. The proforma contained personal data, comorbidities, type of surgery, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 29 publications
3
20
1
2
Order By: Relevance
“…In our study, the incidence of all types of SSI after cardiac surgery was quite high (29.3%). Fortunately, deep infection and osteomyelitis were low (5.7% and 1.3%, respectively), which is consistent with the numbers in the literature [3,5,16]. Interestingly, in our cohort, there was a higher incidence of gram-negative induced infections compared to gram-positive (43% vs. 25.4%).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In our study, the incidence of all types of SSI after cardiac surgery was quite high (29.3%). Fortunately, deep infection and osteomyelitis were low (5.7% and 1.3%, respectively), which is consistent with the numbers in the literature [3,5,16]. Interestingly, in our cohort, there was a higher incidence of gram-negative induced infections compared to gram-positive (43% vs. 25.4%).…”
Section: Discussionsupporting
confidence: 92%
“…This is quite different from the published literature where gram-positive induced infections are predominant [2][3][4][5][6]17]. In a locally conducted retrospective cohort study by Al Majid et al in Riyadh, with 1241 adult patients who underwent cardiac surgery in a singlecenter, the incidence of SSI was 3.2% with 45% of infections due to methicillin-susceptible Staphylococcus aureus [5]. They found that neither gender, obesity, diabetes mellitus, non-use of statins, nor CABG surgery were significant predictors of infection.…”
Section: Discussioncontrasting
confidence: 90%
See 3 more Smart Citations